A study on engine performance operating on compressed biogas - Mel, Maizirwan; Osman, Muhammad Irfan; Ihsan, Sany Izan; Hassan, Md Sadikin (Knowledge Transfer Programme © Knowledge Transfer Centre, 2007)
Methane is similar in energy content compared to gasoline. Therefore, methane is suitable to be paired or replaced with existing Internal Combustion (IC) engine with slight modification. When compared with gasoline in terms of RON, methane gas is much higher. Such quality in vital in producing high power and high compression Spark Ignition (SI) of engine. Therefore, exploiting the methane gas characteristic is crucial in developing a greener energy consumption for our substance. Generally, this paper consist of two phases of experiment where first phase will be the compression stage to store biogas in a pressurized state in order to obtain desired energy content, and the second phase which involves the biogas testing in an IC engine. The challenge would be selecting the best IC engine to run on the compressed biogas adequately. This report will focus more on the engine performance in terms of brake horse power (BHP), efficiency and fuel consumption. Care also be taken to include the side effect of using methane gas on IC engines. The result has shown that the methane gas as fuel where BHP, torque, efficiency and fuel consumption are lower than used gasoline, but top speed for the both are similar. As conclusion that methane has a big potential to replace gasoline as low carbon fuel.